2008
DOI: 10.1186/1471-2180-8-173
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of biofilm matrix, degradation by DNase treatment and evidence of capsule downregulation in Streptococcus pneumoniae clinical isolates

Abstract: Background: Streptococcus pneumoniae is a common respiratory pathogen and a major causative agent of respiratory infections, including otitis media (OM). Pneumococcal biofilms have been demonstrated on biopsies of the middle ear mucosa in children receiving tympanostomy tubes, supporting the hypothesis that chronic OM may involve biofilm development by pathogenic bacteria as part of the infectious process. To better understand pneumococcal biofilm formation six low-passage encapsulated nasopharyngeal isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
217
4
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(244 citation statements)
references
References 45 publications
21
217
4
2
Order By: Relevance
“…Although we could not determine the MIC of the bacteria present in the tissue, since MIC is measured on planktonic cells, we know from Thornsberry et al (64) that the MIC 90 for H. influenzae is 2 g/ml (1,032 isolates tested), that for S. pneumoniae is 16 g/ml (1,275 isolates tested), and that for M. catarrhalis is 0.12 g/ml (444 isolates tested). However, bacteria in biofilms are often over 100 times more resistant to antibiotics (14,23,29,65). We therefore used 2 mg/ml because it is Ͼ125 times the MIC 90 of the most common respiratory pathogens and should sufficiently test whether biofilm bacteria demonstrated increased recalcitrance to antibiotic.…”
Section: Patientmentioning
confidence: 99%
“…Although we could not determine the MIC of the bacteria present in the tissue, since MIC is measured on planktonic cells, we know from Thornsberry et al (64) that the MIC 90 for H. influenzae is 2 g/ml (1,032 isolates tested), that for S. pneumoniae is 16 g/ml (1,275 isolates tested), and that for M. catarrhalis is 0.12 g/ml (444 isolates tested). However, bacteria in biofilms are often over 100 times more resistant to antibiotics (14,23,29,65). We therefore used 2 mg/ml because it is Ͼ125 times the MIC 90 of the most common respiratory pathogens and should sufficiently test whether biofilm bacteria demonstrated increased recalcitrance to antibiotic.…”
Section: Patientmentioning
confidence: 99%
“…Therefore, the employment of PE-depolymerising agents such as gelsolin and thymosin beta 4 or DNase 1 used for dissolution of biofilm-stimulating F-actin and DNA, respectively, might constitute an interesting approach in the eradication of microbial communities [62][63][64]. The statement that the presence of eDNA is crucial for the biofilm formation and structural integrity is additionally established by the reports demonstrating that the treatment with DNase 1 reduces the attachment of microbial cells to the surface, inhibits the biofilm development, and reduces the mass of mature biofilm [65], which is determined by the impairment of cell-to-cell adhesion and joining elements in microbial aggregates [66,67]. Importantly, the co-administration of antimicrobial agents with factors that have the ability to disassemble the biofilm polyelectrolyte network, including DNase 1, considerably improves their antibacterial efficiency [5,68].…”
Section: Dna and F-actin In Bacterial Biofilm Developmentmentioning
confidence: 98%
“…e authors revealed that the average bio�lm thickness was reduced by 85%-97%, indicating that, within the bio�lm, areas composed of lower amounts of extracellular DNA in comparison to adherent cells exist [80].…”
Section: Deoxyribonuclease Imentioning
confidence: 99%
“…Furthermore, Hall-Stoodley et al [80] reported that DNase I induced bio�lm degradation by 66.7%-95% for six clinical isolates of Streptococcus pneumoniae, even though the bio�lms were grown for six days. e authors revealed that the average bio�lm thickness was reduced by 85%-97%, indicating that, within the bio�lm, areas composed of lower amounts of extracellular DNA in comparison to adherent cells exist [80].…”
Section: Deoxyribonuclease Imentioning
confidence: 99%